PERANGKAP KEMISKINAN PADA WARGA RELOKASI (STUDI KORELASIONAL: UNSUR-UNSUR PERANGKAP KEMISKINAN PADA WARGA RELOKASI PUCANG MOJO KEDUNGTUNGKUL MOJOSONGO JEBRES SURAKARTA) - Nurcahyono, Okta Hadi; Slamet, Y; zuber, ahmad (Jurnal Analisa Sosiologi, 2015)
This study is the result of the interpretation of the theory of "Poverty Trap" Robert Chambers (1983) to the social facts paradigm (Emile Dhurkheim, 1964). The purpose of this study was to determine whether or not the resident relocation poverty trap, by way of explaining whether or not the relationship between the elements of the poverty trap in this case: powerlessness, vulnerability, physical weakness, material poverty, and isolation of the Public Service, the citizens relocation Pucang Mojo, Kedungtungkul, Mojosongo, Surakarta. This study uses poverty approach both structurally and culturally. This research is survey research with an explanatory strategy. The study population was all heads of households in Housing Relocation Pucang mojo, Mojosongo, Surakarta.The number of sample was taken 50% out of total population. This study employed quantitative data with triangulation using qualitative data as the confirmer. The qualitative data used was the one derived from result of interview and observation. To examine the relationship between the elements of poverty trap, Product Moment Correlation test was used that was processed with SPSS 19.0 version IBM. The dominant result of statistic data processing in this study was then combined with qualitative data in the discussion. The result of discussion showed that: out of ten relationships between variables or elements existing, only four categorized into significant relationship, while the other six elements were proved insignificant. The four elements are shown to have a significant association among others: the poverty of material with physical weakness, material poverty with vulnerability, physical weakness with vulnerability, and isolation of the public service with the helplessness while the sixth has no correlation relationships such as: poverty with insulating material to public servants, the material poverty with powerlessness, physical weakness with insulation against public servants, physical weakness with powerlessness, isolation against public servants with vulnerability, and vulnerability to helplessness. This finding showed that not all hypotheses suggested by Robert Chambers (1983) could be proved in the context of urban poverty, particularly among the relocated people in Pucangmojo, Kedungtungkul, Mojosongo, Jebres, Surakarta.Â Keywords: poverty trap andÂ